A Study to Assess the Effectiveness of Structured Teaching Program on Knowledge Regarding Antenatal Care among the Pregnant Women of Silk Mill PHC, Chh. Sambhajinagar - Amarja Gosavi; Charushila Jadhav (Indian Journal of Nursing Sciences, 2025)
Background: Maternal and child health promotion is a key component of India’s Family Welfare Program. Ensuring safe motherhood through quality antenatal care (ANC) is vital for reducing maternal and infant mortality rates and achieving sustainable health goals. Improving knowledge of ANC among pregnant women can lead to better health outcomes for both mother and child. Materials and Methods: A pre-experimental (one-group pre-test, post-test) study was conducted among 30 pregnant women at Silk Mill PHC, Aurangabad, using a non-probability convenient sampling technique. The structured teaching program (STP) was the independent variable, while ANC knowledge was the dependent variable. A validated structured knowledge questionnaire was used to assess ANC knowledge before and after the STP. A pilot study was conducted to ensure feasibility. Data were collected, tabulated, and analyzed using descriptive and inferential statistics. The effectiveness of the STP was evaluated using a paired t-test, while an unpaired t-test and analysis of variance were used to assess associations with demographic variables. Results: The findings revealed that the mean pre-test knowledge score was 7.63, which significantly increased to 15.27 post-intervention. Statistical analysis confirmed that the STP was effective in enhancing ANC knowledge among pregnant women. Conclusion: The study highlights that ANC knowledge among pregnant women is inadequate and demonstrates the effectiveness of STPs in improving maternal awareness. Strengthening ANC education through structured interventions can contribute to healthier pregnancies, safer deliveries, and better maternal and neonatal health outcomes.